2023
DOI: 10.1021/acsnano.3c02477
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time In Situ Observation of CsPbBr3 Perovskite Nanoplatelets Transforming into Nanosheets

Abstract: The manipulation of nano-objects through heating is an effective strategy for inducing structural modifications and therefore changing the optoelectronic properties of semiconducting materials. Despite its potential, the underlying mechanism of the structural transformations remains elusive, largely due to the challenges associated with their in situ observations. To address these issues, we synthesize temperature-sensitive CsPbBr3 perovskite nanoplatelets and investigate their structural evolution at the nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…This initial decomposition and restructuring behavior is directly responsible for the subsequent formation of coffee-ring structures (see the following text), which can be understood from the following aspects. First and most importantly, as the synthesis of halide perovskite NCs always involves the addition of capping agents (OA/OAm in our situation), the surfaces of NCs are generally covered by these agents (although they are invisible in TEM images). , These long-chain agents themselves, as organic structures, are extremely unstable under electron beam irradiation; furthermore, they have the chance to distort the surface lattices of NCs, leading to prior degradation of surface Cs 4 PbBr 6 into PbBr 2 before the interior of NCs. Second, it is well-known that the surfaces of NCs are energitically unstable as compared to the internal region .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This initial decomposition and restructuring behavior is directly responsible for the subsequent formation of coffee-ring structures (see the following text), which can be understood from the following aspects. First and most importantly, as the synthesis of halide perovskite NCs always involves the addition of capping agents (OA/OAm in our situation), the surfaces of NCs are generally covered by these agents (although they are invisible in TEM images). , These long-chain agents themselves, as organic structures, are extremely unstable under electron beam irradiation; furthermore, they have the chance to distort the surface lattices of NCs, leading to prior degradation of surface Cs 4 PbBr 6 into PbBr 2 before the interior of NCs. Second, it is well-known that the surfaces of NCs are energitically unstable as compared to the internal region .…”
mentioning
confidence: 99%
“…In this context, state-of-the-art in situ transmission electron microscopy (TEM) techniques have allowed real-time observations of structural evolution under various stimuli (beam irradiation, heating, biasing, gas or even liquid, etc. ), which have been adopted in the study of structural instability and degradation mechanisms of perovskite nanomaterials. Arciniegas et al observed heat-induced transformation of CsPbBr 3 nanoplatelets that underwent morphological changes to form nanosheets and revealed its various merging pathways . Manna et al reported the structural decomposition of inorganic CsPbBr 3 nanocrystals (NCs) with different shapes and sizes, which underwent a radiolysis process and ultimately produced high-contrast particles of Pb .…”
mentioning
confidence: 99%
“…Surface effects such as surface defects and surface energy level adjustments may lead to non-radiative transitions or energy dissipation on the crystal surface, resulting in a decrease in fluorescence lifetime. This has been explained by a slight increase in the thickness of the nanosheets . The real-time monitoring of the exchange process between (PEA) 2 PbBr 4 nanosheets and CsOA is shown in Figure d.…”
Section: Resultsmentioning
confidence: 94%
“…This has been explained by a slight increase in the thickness of the nanosheets. 39 The real-time monitoring of the exchange process between (PEA) 2 PbBr 4 nanosheets and CsOA is shown in Figure 2d. We observed that the two-dimensional characteristic emission peak at 412 nm remained throughout the entire process while the multi-dimensional (n = 2, 3) peaks corresponding to CsPbBr 3 appeared within 2 min.…”
Section: Resultsmentioning
confidence: 99%
“…We have determined the photoluminescence quantum yield (PLQY) for Cs 4 PbI 6 NCs using eq . PLQY 0 normalD = N emit N absorb For this purpose, the number of emitted ( N emit ) photons for 0D Cs 4 PbI 6 NCs and absorbed ( N absorb ) photons for 0D Cs 4 PbI 6 NCs were determined using an absolute PLQY spectrometer (Hamamatsu). Table indicates that the PLQY value for 0D Cs 4 PbI 6 NCs is 49%.…”
Section: Resultsmentioning
confidence: 99%